The PALB2 gene is a strong candidate for clinical testing in BRCA1- and BRCA2-negative hereditary breast cancer - Janatova, Marketa; Kleibl, Zdenek; Stribrna, Jana; Panczak, Ales; Vesela, Kamila; Zimovjanova, Martina; Kleiblova, Petra; Dundr, Pavel; Soukupova, Jana; Pohlreich, Petr (Cancer epidemiology, biomarkers & prevention, 2013)
BACKGROUND: Several reports indicate that inherited mutations in the PALB2 gene predispose to breast cancer. However, there is little agreement about the clinical relevance and usefulness of mutation screening in this gene. We analyzed the prevalence and spectrum of germline mutations in PALB2 to estimate their contribution to hereditary breast and/or ovarian cancer in the Czech Republic. METHODS: The entire PALB2 coding region was sequenced in 409 breast/ovarian cancer patients negative for BRCA1 and BRCA2 mutations. Testing for large genomic rearrangements (LGR) was performed by multiplex ligation-dependent probe amplification (MLPA) analysis. RESULTS: We have identified 13 different pathogenic alterations including 10 truncating mutations and three LGRs in 16 of 409 patients (3.9%), whereas one truncating mutation was found in a group of 1,226 controls (0.08%; P = 2.6 × 10(-9)). Three novel LGRs included deletions involving exons 7-8 and 9-10, respectively, and a duplication spanning exons 9-11. Five frameshift and two nonsense mutations were novel, whereas three truncating mutations were described previously. The only recurrent mutation was the c.172_175delTTGT detected in four unrelated breast cancer individuals. CONCLUSIONS: Our analyses demonstrated the significant role of the PALB2 gene in breast cancer susceptibility. The highest frequency of PALB2 mutations (comparable with that previously reported for BRCA2) was found in a subgroup of patients with hereditary breast cancer (HBC) (13/235; 5.5%). IMPACT: Our results show that mutation analysis of the PALB2 gene, including the analysis of LGRs, is primarily indicated in patients with HBC in case of their BRCA1 and BRCA2 negativity.
Keywords: DNA Mutational Analysis; lidé; Base Sequence; Ovarian Neoplasms; Case-Control Studies; Risk Factors; Genes, BRCA2; Female; Prevalence; Gene Deletion; geny BRCA1; Tumor Suppressor Proteins; Humans; nádory prsu; rodokmen; nádory vaječníků; Breast Neoplasms; nádorové supresorové proteiny; studie případů a kontrol; protein FANCN; delece genu; genetická predispozice k nemoci; Genes, BRCA1; jaderné proteiny; geny BRCA2; Fanconi Anemia Complementation Group N Protein; ženské pohlaví; prevalence; molekulární sekvence - údaje; Pedigree; Molecular Sequence Data; Genetic Predisposition to Disease; mutační analýza DNA; sekvence nukleotidů; rizikové faktory; Nuclear Proteins